Social risk factors and protection against adolescent suicide - Bravo Andrade, Héctor Rubén (2018)
The phenomenon of adolescent suicide involves social and contextual issues that need to be enriched in a specialized literature, so the aim of the current research was to know the social risk and protective factors associated with this problem. A qualitative study was conducted through focus groups conformed by students, teachers and psychotherapists, chosen through a convenience sampling. Through qualitative data coding, emerged as social risk factors mass media, especially the internet, as well as been involved in a bullying situation. On the other hand, factors such as peer group, school and social context were identified as elements that can represent both risk and protective factors. It is discussed, the need of taking actions in order to develop positive interactions from a health promotion approach.